2021
DOI: 10.1007/s11696-021-01848-9
|View full text |Cite
|
Sign up to set email alerts
|

Purification of recovered phosphoric acid by extracting aluminium with di-2-ethylhexyl phosphoric acid

Abstract: The extraction of aluminium from dilute phosphoric acid with di-2-ethylhexyl phosphoric acid (DEHPA) was optimized using response surface methodology. The optimization was based on the experimental three-level central composite face-centred design (CCF) and was conducted on real-life samples. The three variables included were pH, extractant concentration and aqueous to organic phase ratio (AO). Under the optimized conditions (pH 2.5, 0.6 M DEHPA and AO ratio 1:2), extraction efficiency of 99% for aluminium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In general, it was observed that Al 3+ and Fe 3+ remained in the D2EPHA. This recalcitrant stripping of Fe 3+ and Al 3+ from D2EPHA has been reported [53,54]. However, the stripping of metals from higher concentrated extractant (40% v/v D2EPHA) was investigated (Figure 8b).…”
Section: Conceptual Flow Sheetsupporting
confidence: 63%
“…In general, it was observed that Al 3+ and Fe 3+ remained in the D2EPHA. This recalcitrant stripping of Fe 3+ and Al 3+ from D2EPHA has been reported [53,54]. However, the stripping of metals from higher concentrated extractant (40% v/v D2EPHA) was investigated (Figure 8b).…”
Section: Conceptual Flow Sheetsupporting
confidence: 63%
“…In these industrial applications, the purity requirement for PA, especially for wet-process phosphoric acid (WPA), is extremely high. Some techniques for purifying PA have recently been developed, such as crystallization [2,3], ion exchange [4,5], adsorption [6,7], and solvent extraction [8][9][10]. Among these, solvent extraction is an ideal purifying approach because of its low energy consumption, comparatively simpler production technology and equipment, and ease of automating batch production.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse on/off time, wire feed, gap voltage, and the relative atomic number (Ra) of the metal removed are all variables that have been shown to influence MRR. [15][16] With increasing SiC volume, MRR reduced and Ra increased, according to experiments conducted with L9 OA, which is employed for the research in this paper. The effects of pulse on time, pulse off time, and wire speed on reinforcement of fly ash were studied [17] at a range of weight percentiles.…”
Section: Introductionmentioning
confidence: 99%